Comparative effectiveness research on incision healing after lumbar spinal surgery with different TDP irradiation durations - Xiao Feng; Jiang Ren-Lian; Chen Jun-Ru; Long Xue-Mei (Sciendo, 2018)
This research aims to investigate the best "Te Ding Dian Ci Bo Pu Zhi Liao Qi" (TDP) irradiation duration to enhance the efficacy of nursing and patient satisfaction.